Gente,de novo eu preciso confirmar uma resposta com vcs:
-x²+(m-1)x+3=0
Δ=mx-x-4*-3
Depois de toda a conta:Δ=m+12
É assim?
Respostas
respondido por:
1
Delta=(m-1)^2-4.-1.3
=m^-2m+1-4
=m^2-2m-3
Delta =-2^2-4.1.-3
=4+12
Delta =16
m=(-2+-4)/2
m'=(-2+4)/2= 1
m"=(-2-4)/2=-3
=m^-2m+1-4
=m^2-2m-3
Delta =-2^2-4.1.-3
=4+12
Delta =16
m=(-2+-4)/2
m'=(-2+4)/2= 1
m"=(-2-4)/2=-3
stefanyellen:
Ah,agora entendi,obrigado ^^
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás